Rolling to control residual stress and distortion in friction stir welds - Wen, S. W.; Colegrove, Paul A.; Williams, Stewart W.; Morgan, S. A.; Wescott, A.; Poad, M. (Cranfield University, 2010)
Considerable residual stress and distortion can be produced by friction stir welding, impeding industrial implementation. Finite element analysis has been used to develop three innovative rolling methods that reduce residual stress and distortion in friction stir welds. Of the three methods, post-weld direct rolling where a single roller is applied to roll the top surface of the weld after the weld metal has cooled to room temperature proved the most effective. The residual stress predictions from the model compared favourably with residual stress measurements reported in an accompanying paper. Finally, the effectiveness of using post-weld direct rolling is illustrated with an industrial example of a large integrally stiffened panel, where the distortion was virtually eliminated.
Keywords: Rolling Friction stir weld Residual stress Distortion Finite element modelling temperature simulation roller alloy amg6 arc